Study of the mechanism of change in flavonoid composition in the processing of Chrysanthemum morifolium (Ramat.) Tzvel. ‘Boju’ - Zhang, Wei (BMC Chem, 2019)
A form of β-glucosidase was isolated and purified from fresh Chrysanthemum morifolium (Ramat.) Tzvel. ‘Boju’ (Boju) and its enzymatic properties explored in this study. The purified enzyme and Boju flavonoids were reacted in a water bath to ascertain the composition of the reactants. Flavonoid glycoside and aglycon concentrations in Boju varied significantly depending on processing method. The concentration of flavonoid glycosides in Boju decreased and flavonoid aglycons increased due to heat-activation of β-glucosidase which hydrolyzed the flavonoid glycosides in Boju to aglycons.